On Coccophagoides Girault and Diaspiniphagus Silvestri (Hymenoptera: Chalcidoidea: Aphelinidae) - Hayat, Mohammad (Zootaxa, 2011)
The aphelinid genus Diaspiniphagus Silvestri is considered a valid taxon, distinct from Coccophagoides Girault. Both genera are briefly diagnosed and the world species are listed. Diaspiniphagus is newly recorded from India and a new species, D. decorus sp. nov., is described. The following species are transferred to Diaspiniphagus as new combinations: D. inlacertus (Girault) from CoccophagusWestwood and D. fasciativentris (Girault), D. forbesi (Dozier), D. fuscipennis (Girault), and D. pulchellus (Dozier) from Prospaltella Ashmead.